Characteristics of the Health Information Technology Workforce in Georgia - Imaobong Ekpo; Emmanuel Akowuah; Bettye Apenteng; Samuel Opoku (Georgia Southern University, 2019)
Background: Advancement in medical technology, as well as the Health Information Technology for Economic and Clinical Health Act, has in part influenced the demand for health information technology (HIT) workers. While other sectors have experienced a tremendous increase in the information technology workforce, the health sector lags in this regard. The aim of this study was to describe the characteristics of the HIT workforce in Georgia, relative to surrounding states and the United States. Methods: The supply of the HIT workforce in Georgia, surrounding states, and the United States was estimated using data from the 2014-2016 American Community Survey (ACS). The 2010 ACS Occupation Codes and 2012 ACS Industry Codes were used to identify the HIT workforce. Population data for 2015, obtained from the US Census Bureau was used for standardization of the total supply of the HIT workforce. Data were analyzed using Stata 14.0. Results: The number of HIT workforce supply for Georgia (206.4 per 100,000 population) trails national (275.4 per 100,000) and regional (233 per 100,000) estimates. In terms of demographic characteristics, Georgia has a more racially diverse HIT workforce, compared to the surrounding states and the nation but lacked Hispanic representation. Additionally, compared to the surrounding states and the US, Georgia has a higher proportion of females in this workforce (80.9%). Most HIT workers are employed in hospitals and work full-time. Conclusions: The supply of the HIT workforce in Georgia currently trails regional and national estimates. With the advancements in medical technology and the HITECH Act, there is an increasing demand for health information technology workers. As such, attention should be paid to recruitment and retention efforts. This report may serve as a reference for future evaluation and monitoring of trends in the HIT workforce in the state. Keywords: Health information technology, medical technology, supply, workforce, demographics